The political affordances of the ‘coconut wireless’: Rotumans on social media in the 2018 Fiji elections - Rufino Varea (Asia Pacific Network, 2020)
As a unique group of people, Rotumans make up less than two percent of Fiji’s population, and as a minority Indigenous ethnic group in Fiji, they have remained relatively hidden and silent in political affairs. Outmigration from the island has led to more than 80 percent of Rotumans residing outside of Rotuma. In recent times, the Rotuman diaspora has heavily relied on the use of ICTs and new media technologies as crucial tools for the reinvigoration of Rotuma’s culture. This in itself poses an intriguing paradox as internet connectivity on Rotuma is quite limited. However, social media platforms have been increasingly used by Rotumans outside of Rotuma, and have enabled increased connectivity and greater dissemination of information among the Rotuman diaspora. Recently, the primary purpose of such social media groups has evolved from merely being a tool for rekindling familial ties, to being a platform for political discourse on Rotuman issues. In essence, despite the scattered nature of the Rotuman population, digital technologies are offering Rotumans the affordance of being able to inform and educate themselves and their networks on political issues of Rotuman interest. By employing ethnography and netnography principles and through in-person and online engagement with Rotumans within and outside of Rotuma, this article examines the affordances that digital technologies offer Rotumans concerning national political discourse. This is carried out with a specific focus on the 2018 general elections in Fiji.